2010
DOI: 10.1134/s0026893310030118
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the DNA polymerase and thymidine kinase genes of herpes simplex virus clinical isolates resistant to antiherpetic drugs

Abstract: Association of deletion polymorphism in GSTT1 and GSTM1 genes and polymorphic variant A313G of GSTP1 gene with cirrhosis diseases and 4-year survival rate for the Tomsk region (West Siberia) patients were tested. Homozygous deletion of GSTM1 gene (null genotype) was a protective factor for alcoholic and mixed (HCV, HBV and alcohol) liver cirrhosis development. The patients from the joint group (all etiology forms) as well as having alcoholic and mixed cirrhosis had lower frequency of GSTM1 null genotype (39.2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Such an enzyme is incapable of catalyzing the first step of ACV phosphorylation required for its conversion into active metabolite ACV triphosphate, which is capable of incorporating into a newly synthesized viral DNA chain and aborting its elongation through the mechanism of termination. Deletion deltaT66 was found in the UL23 gene of the Avd strain located in close vicinity to the ATP-binding site of the enzyme (amino acid residues 51–63), which may cause a decrease in ACV phosphorylation efficiency [ 20 , 25 ]. The obtained results confirm that all the ACV-resistant HSV strains included in the study exhibit a TK-deficient phenotype and allow one to suggest that mutations in the nucleoside binding site and ATP-binding center do not substantially affect the metabolic conversions of Hp-ACG to monophosphate of ACV, which, like ACV, is further converted into diand triphosphate of ACV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such an enzyme is incapable of catalyzing the first step of ACV phosphorylation required for its conversion into active metabolite ACV triphosphate, which is capable of incorporating into a newly synthesized viral DNA chain and aborting its elongation through the mechanism of termination. Deletion deltaT66 was found in the UL23 gene of the Avd strain located in close vicinity to the ATP-binding site of the enzyme (amino acid residues 51–63), which may cause a decrease in ACV phosphorylation efficiency [ 20 , 25 ]. The obtained results confirm that all the ACV-resistant HSV strains included in the study exhibit a TK-deficient phenotype and allow one to suggest that mutations in the nucleoside binding site and ATP-binding center do not substantially affect the metabolic conversions of Hp-ACG to monophosphate of ACV, which, like ACV, is further converted into diand triphosphate of ACV.…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxicity was evaluated in accordance with the conventional trypan blue exclusion method of cell staining [ 20 , 21 ]. CTD50 was considered to be the substance concentration which ensured the death of 50% the cells after 72 h of incubation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this position is located within a highly conserved catalytic site of the TK (Figure 3 ). 4 Therefore, clinical resistance to VACV is suspected to be induced by W89G TK mutation rather than R628C DNA pol mutation. A second‐line treatment by intravenous foscarnet (FOS) was initiated at weight‐adjusted dosing due to obesity according to pharmacists' guidelines.…”
Section: Figurementioning
confidence: 99%
“…Ghobadloo et al [ 82 ] discovered the association of cryptogenic cirrhosis with Val/Val GSTP1 genotype which might be explained by low detoxification activity of protein that implicate this polymorphism as a risk factor for occurrence of the disease. Goncharova et al [ 83 ] showed that patients with liver cirrhosis AA genotype carriers have 2.5 times higher survival rate compared with the patients with the GG and AG genotypes of GSTP1 gene.…”
Section: Liver Cirrhosismentioning
confidence: 99%